Money Can't Buy EU Love: European Funds and the Brexit Referendum - Jan Fidrmuc; Martin Hulényi; Cigdem Börke Tunali (Center for Economic Studies and ifo Institute (CESifo), 2016)
We explore the role of the transfers that UK regions received from the European structural and cohesion funds, as well as other economic and social factors, in determining the support for the Remain vote in the Brexit referendum. We .nd that past European transfers have played virtually no role in the referendum. Economically strong regions tend to be in favor of remaining in the EU. Somewhat surprisingly, the intensity of immigration from the EU is positively correlated with the Remain vote.
Keywords: D72; F02; F15; 330; European integration; economic voting; cohesion policy